2005
DOI: 10.1002/hyp.5594
|View full text |Cite
|
Sign up to set email alerts
|

A novel hysteresis model in unsaturated soil

Abstract: Abstract:This study presents a novel hysteresis model based on van Genuchten's soil-moisture relationships. The proposed model yields a series of closed-form relationships in which two shape factors˛and Á are determined from the main drying and wetting curves. Experimental and literature-cited data were used to assess model accuracy. The proposed model was also compared with the Scott and KP models. Analytical results indicate that the present model is simple, accurate and effective in constructing the series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 14 publications
2
101
1
2
Order By: Relevance
“…Temporal variability of intensity within the same rainfall event could induce drainage and redistribution to occur simultaneously in the same soil profile. Consequently, hysteresis in the () relationship [Haines, 1930;Everett, 1955;Poulovassilis, 1962;Topp, 1971;Mualem, 1974;Mualem and Dagan, 1975;Parlange, 1976;Hogarth et al, 1988;Nimmo, 1992;Huang et al, 2005;Mualem and Beriozkin, 2009] would play a crucial role in the accurate description of the flow processes within that soil profile [Ibrahim and Brutsaert, 1968;Hanks et al, 1969;Scott et al, 1983;Glass et al, 1989]. The capability to describe the ensemble of scanning curves within the hysteresis loop is necessary to achieve any reliable quantitative treatment of the flow process.…”
Section: Infiltration Under Special Conditionsmentioning
confidence: 99%
“…Temporal variability of intensity within the same rainfall event could induce drainage and redistribution to occur simultaneously in the same soil profile. Consequently, hysteresis in the () relationship [Haines, 1930;Everett, 1955;Poulovassilis, 1962;Topp, 1971;Mualem, 1974;Mualem and Dagan, 1975;Parlange, 1976;Hogarth et al, 1988;Nimmo, 1992;Huang et al, 2005;Mualem and Beriozkin, 2009] would play a crucial role in the accurate description of the flow processes within that soil profile [Ibrahim and Brutsaert, 1968;Hanks et al, 1969;Scott et al, 1983;Glass et al, 1989]. The capability to describe the ensemble of scanning curves within the hysteresis loop is necessary to achieve any reliable quantitative treatment of the flow process.…”
Section: Infiltration Under Special Conditionsmentioning
confidence: 99%
“…Numerous models have been developed in order to describe the hysteretic behavior of a particular soil [15][16][17][18]. In the present study we used the modified Kool and Parker model [17] developed by Huang et al [18]. This model of simple formulation uses α, n, …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, the present research explored completely the possible effect of hysteresis on the relationship between soil water content and matric suction head, and the effect of hysteresis on the formation of fingered flow was established and verified by laboratory experiment, where the formation of fingered paths was observed in an initially dry soil. We present a soil water content concept model based on experimental evidence and a novel hysteresis model (Huang et al, 2005) to explain the mechanism of the persistence of fingered flow. We have also developed an experimental technique to catch rapid visualization of the changing soil water content in thin slabs of porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have found that a fingered path persists over long periods of constant infiltration; hysteresis could be an important factor. In this paper, a major point is to utilize the boundary and series internal scanning curves of the hysteresis model derived by Huang et al (2005) to clearly obtain the variations between soil water content (u) and matric suction head (c). The hydraulic properties of fingered flow are also acquired.…”
mentioning
confidence: 99%